2018
DOI: 10.1002/app.47177
|View full text |Cite
|
Sign up to set email alerts
|

Loss of thermoplastic elastomer toughening in polylactide after weathering

Abstract: It has been already pointed out that one of the best ways to increase toughness of the inherently brittle polylactide (PLA) without sacrificing strength and modulus is the use of thermoplastic elastomer toughening approach; but what happens under outdoor conditions was not explored. Therefore, the objective of this study was to explore the degree of losses especially in fracture toughness of PLA when blended with thermoplastic polyurethane (TPU) elastomer or thermoplastic polyester elastomer (TPE) after weathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The sample was heated again from 30 to 200 °C at the same increase rate. The second heating curve was recorded, and the crystallinity of PLA was calculated as [ 16 ] where X c represents the crystallinity of PLA, and are the melting enthalpy and cold crystallization enthalpies of the sample, respectively, and and are the melting enthalpy and PLA mass fraction of 100% crystallized PLA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was heated again from 30 to 200 °C at the same increase rate. The second heating curve was recorded, and the crystallinity of PLA was calculated as [ 16 ] where X c represents the crystallinity of PLA, and are the melting enthalpy and cold crystallization enthalpies of the sample, respectively, and and are the melting enthalpy and PLA mass fraction of 100% crystallized PLA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, with in situ fibrillation of TPU in PLA/TPU blends, improvements in the toughness of printed structures were reported due to the generation of TPU fibrils, enhanced PLA crystallization around the fibrillated structures, and hence improved interfacial interactions [45] Considering the long-term behavior of PLA/TPU blends, it has been reported that weathering could cause drastic losses in the strength and toughness of the blends. [46] It is still not very clear in the literature how changes in the TPU molecular structure such as variations in HS content or in the molecular weight of SS could influence the final properties of PLA/TPU blend systems. Therefore, in this study we aimed at exploring how the variations in the HS content of TPUs could influence the morphological, rheological, and mechanical properties of PLA/TPU blends without using any compatibilizer and with using only 15 wt% TPU.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of the processing parameters in Table 1 were chosen to obtain adequate values for the production of electrospun nanofibers, in accordance with previous works that utilized PCL as an electrospinning material. [30][31][32] Furthermore, the optimal processing condition resulted in maximal C R . Therefore, the larger-the-better characteristic was applied to the analysis to find the optimal processing parameters that made C R → 100.…”
Section: Effects Of Electrospinning Processing Parameters On C Rmentioning
confidence: 99%